Spray-induced gene silencing for crop protection: recent advances and emerging trends - Chen, Can; Imran, Muhammad; Feng, Xianyang; Shen, Xihui; Sun, Zhongke (Frontiers in Plant Science, 2025)
The RNA-based spray-induced gene silencing (SIGS) technology represents an ecologically sustainable approach to crop protection and pathogen management. Following the recent approval of Ledprona as the first sprayable double-stranded RNA (dsRNA) biopesticide by the EPA at the end of 2023, SIGS has emerged as a focal point in both academic and industrial sectors. This review analyzes recent advances and emerging trends in SIGS. The application of SIGS for crop protection, including the control of insects, fungal pathogens, and viruses, is briefly summarized. Distinguishing this review from others, we delve into practical aspects of the technology, such as the selection and screening of target genes, large-scale production methods, and delivery systems, highlighting major advancements in these areas and also addressing the remaining questions and issues, particularly concerning safety concerns and controlling harmful weeds. Finally, this review emphasizes the emerging trends in SIGS technology, particularly its integration with nanotechnology and other methodologies. Collectively, the rapid progress in SIGS studies is poised to accelerate the maturation and application of this technology.